Toxigenic Campylobacter jejuni in vegetables farms and retail outlets in Terengganu - Tang, John Yew Huat; Khalid, M. I.; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
This study was conducted to determine the prevalence and antibiotic resistance among toxigenic Campylobacter jejuni in ulam at farms and retail outlets located in Kuala Terengganu, Malaysia. A total of 526 samples (ulam, soil, and fertilizer) were tested for the presence of C. jejuni and the gene for cytolethal distending toxin (cdt) by using a multiplex PCR method. Antibiotic susceptibility to 10 types of antibiotics was determined using the disc diffusion method for 33 C. jejuni isolates. The average prevalence of contaminated samples from farms, wet markets, and supermarkets was 35.29, 52.66, and 69.88%, respectively. The cdt gene was not detected in 24 of the 33 C. jejuni isolates, but 9 isolates harbored cdtC. Antibiotic resistance in C. jejuni isolates was highest to penicillin G (96.97% of isolates) followed by vancomycin (87.88%), ampicillin (75.76%), erythromycin (60.61%), tetracycline (9.09%), amikacin (6.06%), and norfloxacin (3.03%); none of the isolates were resistant to ciprofloxacin, enrofloxacin, and gentamicin. In this study, C. jejuni was present in ulam, and some isolates were highly resistant to some antibiotics except quinolones. Thus, appropriate attention and measures are required to prevent C. jejuni contamination on farms and at retail outlets.